In the Year of the Boar and Jackie Robinson - Lord, Bette; Simont, Marc (New York : HarperCollins, 1984)
In 1947, a Chinese child comes to Brooklyn where she becomes Americanized at school, in her apartment building, and by her love for baseball.
Wilson's Children, October 2010.
Wilson's Junior High School, November 2005.
Notable/Best Books (A.L.A.), June 2000.
School Library Journal, July 2006.
Five Owls, June 2003.
Book Links (A.L.A.), August 2000.
Keywords: Children's stories, American; Chinese Americans -- Fiction; Moving, Household -- Fiction; Schools -- Fiction; Historical fiction; School stories